Strategi perencanaan jaminan kesehatan semesta Kabupaten Banyuwangi - Litawati, Haspilu (FIA UB, 2016)
This study aims to analyze the opportunities and threats in the implementation of health insurance which is currently implemented in Banyuwangi by describing and understanding the conditions of health insurance that is currently implemented. After knowing the current conditions as well as the opportunities and threatss in the implementation, then compiled a scenario along with strategies in order to achieve universal health insurance in Banyuwangi appropriate national targets in 2019. The method used in the form of qualitative descriptive method as a tool for the preparation TAIDA scenario and strategies to deal with any possible scenarios. Based on this analysis, it was found that the most influential aspect modifier and must have come from political and social categories. Obtained four scenarios, the scenario A, scenario B, scenario C , and scenario D. In order to achieve universal health insurance purposes in 2019, required the implementation of appropriate strategies according to the conditions that may occur by the depiction of scenarios have been prepared.